Experimental Investigation into the Capacity of Concentrically Loaded Steel Connections with Pretensioned High-Strength Bolts and Longitudinal Fillet Welds in Combination - Waite, Christopher D.; Shen, Ligang; Soliman, Mohamed; Russell, Bruce W. (Engineering Journal, 2022)
This paper presents the results of an experimental study aiming to investigate the behavior of steel connections that combine pretensioned high-strength bolts and longitudinal fillet welds on a common faying surface. A total of 75 double-shear tension splices were tested under direct tension loading to quantify the effect of various connection variables on the load-deformation behavior of the connection. These variables include the (1) bolt pattern (2×2 and 2×3), (2) bolt size (3/4 in. and 1 in.), (3) bolt grade (ASTM F3125 Grade A325, A490, and F1852), (4) bolt pretensioning method (turn-of-nut and tension control bolts), (5) faying surface class (Class A and B), and (6) weld/bolt strength ratio. The variation in the connection characteristics covered a wide range of weld/bolt strength ratios from 0.50 to 2.00. The bolts were installed in oversized holes, and the specimens were assembled in a negative bearing condition to allow for a maximum slip distance. The load-deformation behavior of the combination connections was recorded and compared to that of the bolted- and welded-only control specimens. In all tests, the addition of welds increased the capacity of the connection. The investigation shows that the capacity of the combination connection with pretensioned high-strength bolts and longitudinal fillet welds can be computed by adding the capacities of the individual connecting elements while considering the strain compatibility.